(untitled) (Research, Society and Development, 2022)
Higher education institutions are encouraged to make efforts to improve pedagogical practices linked to the strengthening of assistance in the Unified Health System (SUS) and to prepare, in dialogue with the services of the care network, students and professionals with knowledge, skills and values ​​to problematize health care, recognizing situations that require shared care actions. In this perspective, some policies have been developed, such as the Program for Reorientation of Professional Training in Health (Pró-Saúde) and the Education Program through Work for Health (PET-Saúde). Such initiatives aim at qualifying the training processes and have assumptions that guide changes, such as interprofessional education (IPE), so this study aims to understand how IPE in health has been addressed within the scope of the Pro and PET-Health Programs. An integrative literature review was carried out in January 2020 in the databases of the Virtual Health Library (BVS) and on the CAPES Periodicals Portal. The results reaffirm the impact of these Programs in strengthening the debate on IPE on the national scene, and point to the stimulation of important elements related to IPE, such as dialogue, approximation, bonding and evaluation. The teaching-service approach stands out as essential, being strengthened by the Programs. However, there are still challenges to be overcome, such as the inclusion of users in health actions and the institutionalization of pedagogical strategies promoted by the Programs in educational institutions.